Meet the parents: Is the Radical Left the Child of the Radical Right? - Grieve-Carlson, Gary (The journal for cultural and religious theory, 2004)
A review of Richard Wolin’s The Seduction of Unreason: The Intellectual Romance with Fascism from Nietzsche to Postmodernism. Princeton University Press, 2004. 375 pp. $29.95 cloth. ISBN: 0-691-11464-1.